A prospective study of hypothyroidism in tribal women of East Godavari, Andhra Pradesh, India - Satyanarayana, Posina Veera Venkata; Acharya, Anand (International Journal of Advances in Medicine, 2018)
Background: Hypothyroidism is usually categorized under iodine deficient disorder. Ever since universal salt iodization programme is adopted in India there is shift in balance from iodine deficiency to sufficiency state. But studies conducted by various authors during post - iodization period indicated that hypothyroidism is still prevalent in India despite of promotion of iodised salt. So due to lack of information on thyroid status of women in East Godavari of Andhra Pradesh. This study has been conducted to study the hypothyroidism in tribal women in this region. Methods: This is a prospective cross-sectional study conducted in the department of General Medicine Konaseema Institute of Medical Science Godavari between July 2015 to November 2017. Based on specific clinical symptoms of hypothyroidism among 4680 women patient who has attended the health camp 864 patients were selected for haematological evaluation.5ml of fasting blood was collected and thyroid function test was done by estimation of T3, T4, and TSH levels in serum by using ROCHE COBASE-411 immunohistochemistry Analyser. Results: Out of 864 women 342(39.50%) women were euthyroid out of that 84(9.72%) were 15 to30yrs of age, 192(22.2%) were between 31 to 45 years of age and 166(19.21%) were between46 to 65yrs. 316(36.57%) women were having subclinical hypothyroidism, among them 48(5.5%) were between 15 to 30yrs of age, 178(20.60%) were between 31 to 45yrs age and rest 90(10.41%) were between 46 to 65yrs of age. 110 patients were suffering from hypothyroidism that is 12.73%, out of that 12 were between 15 to 30yrs of age, 62(7.17) patients were between 31 to 45yrs age and rest were between 46 to 65yrs that is 36(4.16%). Conclusions: In this study we have found that subclinical hypothyroidism is more common than hypothyroidism. Author have also found that thyroid disorder was more common in reproductive age group tribal women in east Godavari dist. of Andhra Pradesh.